Leadership Mentoring Needed! - Ellen B. Buckner (Universidad de La Sabana, 2020)
¡Necesitamos tutoría en liderazgo! Precisamos de assessoria em liderança! Leadership mentoring is needed in nursing to nurture nurse leaders globally. It requires the selfless giving of our time and insight while encouraging us to be open to a new generation of nurses and nursing vision. In addition, leadership mentoring provides us with opportunities for advocacy for our profession and its worldwide mission. Virtual mentoring communities have been developed through Sigma Theta Tau International (Sigma) and the Roy Adaptation Association (RAA). These engage emerging nurse leaders to contribute to their organizations and to the profession of nursing. From frontline clinical practice, to nursing organizational leadership, to health policy development, leadership mentoring means engaging nursing voice. It means investing the time and talent to nurture and teach leadership in new ways with the next generation. Seeking out opportunities for leadership mentoring is the first step! Para citar este editorial / To reference this editorial / Para citar este editorial Buckner EB. Leadership Mentoring Needed! Aquichan. 2019;19(4):e1941. DOI: https://doi.org/10.5294/aqui.2019.19.4.1 Publicado: 30/01/2020